Tuberculosis of the tongue in a patient under treatment with adalimumab - Cintia Mussi Milani; Rafaela Arana; Rafaela Sávio Melzer; Antônio Adilson Soares Lima; Maria Angela Naval Machado; Liliane Roskamp (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial)
Tuberculosis is a chronic infectious disease that may affect any part of the body, including the oral cavity. Among the predisposing factors to the disease, adalimumab, a monoclonal antibody used as an effective therapy in patients with rheumatic disorders, including psoriatic arthritis, increases the risk of active tuberculosis development. Oral tuberculosis is relatively rare and usually manifests as a persistent oral ulcer. Dentists are at the frontline to diagnose oral lesions and should always consider tuberculosis in the differential diagnosis of a persistent oral ulcer, especially in patients under adalimumab. We present a case of tuberculosis of the tongue in a 50-year-old male under treatment with adalimumab for five years to treat psoriatic arthritis.